2018
DOI: 10.12659/aot.909359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Graft Mechanical Function Using Speckle-Tracking Echocardiography During the First Year After Orthotropic Heart Transplantation

Abstract: BackgroundRecent advances in ultrasound strain imaging facilitate more precise monitoring of subtle myocardial changes and thus may allow for more appropriate assessment of myocardium after orthotopic heart transplantation (OHT). This study aimed to explore longitudinal left ventricular (LV) and right ventricular (RV) function by speckle-tracking echocardiography (STE) during a 12-month follow-up period in relation to acute cellular rejection (ACR) degree ≥2R and the response to intense immunosuppressive thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…This finding was not influenced by exclusion of patient with PH or elevated mRAP at 1 month, suggesting that the observed improvement in echocardiographically measured RV function parameters is not dependent on either PH or elevated mRAP. The gradual improvement in RV strain parameters, albeit not the absolute values, is comparable to previous published data (Antonczyk et al, 2018). Initially, patients pre-treated with LVAD showed slightly better RV function parameters and less improvement during follow-up than the rest of the cohort.…”
Section: Rv Adaptation During the First Year Post-ohtsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding was not influenced by exclusion of patient with PH or elevated mRAP at 1 month, suggesting that the observed improvement in echocardiographically measured RV function parameters is not dependent on either PH or elevated mRAP. The gradual improvement in RV strain parameters, albeit not the absolute values, is comparable to previous published data (Antonczyk et al, 2018). Initially, patients pre-treated with LVAD showed slightly better RV function parameters and less improvement during follow-up than the rest of the cohort.…”
Section: Rv Adaptation During the First Year Post-ohtsupporting
confidence: 87%
“…It has been reported that strain values correlate to major adverse cardiac events and that failure to improve LV global longitudinal strain (GLS) at 3 months after OHT comprise a higher risk for hospitalization and death following transplantation (Clemmensen, Eiskjaer, Logstrup, Ilkjaer, & Poulsen, 2017;Clemmensen, Logstrup, Eiskjaer, & Poulsen, 2015;Eleid et al, 2010). Ventricular adaptation in the early time period following OHT is sparsely studied, and reports exploring the natural time course of ventricular contractile recovery show conflicting results (Antonczyk et al, 2018;Lunze et al, 2012;Ran, Zhang, Ma, Dong, & Wu, 2020). Hence, more insight into the timeframe taken until ventricular adaptation reaches a 'steady state' after OHT is warranted to improve the clinical value of TTE in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…17 Vale ressaltar que os valores de SLG VE, mesmo no grupo 0R do nosso estudo, excederam as faixas relatadas como normais após TC na literatura. 18,19 Avaliação de parâmetros do VD como potenciais marcadores de rejeição subclínica foi relativamente menos explorada em estudos prévios. Clemmensen et al estudaram um grupo de 36 pacientes de TC, achando que a TAPSE foi reduzida no grupo com rejeição celular.…”
Section: Resultsunclassified
“…In our study, the pooled results showed that RS had no relation to ACAR which are in accordance with most previously published data. Antończyk et al 42 reported that RS remained unchanged during within 12 months after HTX and preserved RS might be responsible for maintaining cardiac function in HTX patients. This finding indicates that early stages of edema or fibrosis involve subendocardial myocardial muscle fibers, which leads to attenuation of longitudinal myocardial function only.…”
Section: Discussionmentioning
confidence: 99%